Extracción de pectina de dos variedades de cáscaras de sandía (Citrullus lanatus) costeña y regional - Flores Salazar, Diego Celito (2023)
The present research was carried out in the Research Center of Amazonian Natural Resources (CIRNA) and the other part in the pilot canning plant of the F.I.A, for which samples of regional and coastal watermelon were used, which were acquired in the house of ex-agrarian bank, located between Requena / Pablo Rosell street, then we worked the experimental part of the extraction of pectins starting from the regional watermelon and coastal watermelon, being the method of extraction by acid hydrolysis, being the constant process flow, varying the pH (varying 1.0 and 1.7), time (60 minutes) and temperature (80-95oC), to then perform the analysis of pectins as pH (20oC): 1.84 S.R, 1.10 SC, ash content: 2.85% S.R and 1.05% S.C, free acidity (milliequivalents. carboxyls. free): 1.96 S.R and 1.23 S.C, having the methoxyl content 2.10 S.R and 4.27 S.C, the moisture content is: 6.20 S.R and 3.05 S.C, being the pectin yield of 0.13% and 0.37%, starting from 425 grams of regional watermelon and 453.33 grams of coastal watermelon, having that by the methoxyl content is a low methoxyl pectin (LM < 50%), requiring low sugar content and low in calories, for coagulation in jams, low sugar jellies, in reference to high methoxyl pectins (> 50%), This is used high sugar content and calories not suitable for diabetics.